Answer: x=3
Step-by-step explanation:
To find the zeros, you want to first factor the expression.
x³+x²-36
(x-3)(x²+4x+12)
Now that we have found the factors, we set each to 0.
x-3=0
x=3
Since x²+4x+12 cannot be factored, we can forget about this part.
Therefore, the zeros are x=3. You can check this by plugging the expression into a graphing calculator to see the zeros.
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
<span> 5*(x-2)-4*(x+1)-(50)=0 </span>
Answer:
x=8
Step-by-step explanation:
29x+14= -131
29x=-131-14
x=-145/29
x=-5